Using Augmented Reality Virtual Assistants to Teach the Traditional Leather Tanning Process - Carvalho, Elizabeth, Simão (2011)
The leather tanning process carries a high cultural value in Guimarães city. In some areas of Portugal, most of the society and its history are somehow interlaced with the history of the leather and all the associated processes of its production. There is a great lack of a “vivid” memory about the leather tanning process and its social implications. References to it in Guimarães city can be reduced to text and poor quality pictures. On the other hand, it is important to transmit to future generations the valuable role of the leather tanning in the local culture. At this point, the use of augmented reality techniques can help to illustrate interactively, expressively and with a compelling degree of immersion how this process used to be done, and help to preserve its memory. This project consisted in the development and implementation of an augmented reality application to young audiences that illustrates the ancient leather tanning process step-by-step. The resulting visualizations offer an impressive education experience that help to transfer a significant culture value of the Guimarães city.